Peran dan Profesionalitas Guru Dalam Kegiatan Praktikum Kelas X Pada Jurusan Teknik Ketenagalistrikan di SMK Negeri 4 Bandung - Fadjar Muhammad Ikhsan; Naufal Nadhif Rabbani Iskandar; Randy Amadea Sukma; Wimbow Hatorangan Petra Simamora; Yudhista Karostiawan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
There are 7 types of education in Indonesia, namely, general, vocational, academic, professional, vocational, religious, and special education. Vocational High School (SMK) is one of the education choices of the Indonesian people after graduating from the Junior High School (SMP) level equivalent. The role of teachers in practicum activities at Vocational High Schools (SMK), one of which is practicum, is very important. The role of the teacher in order to supervise practicum activities so that accidents and unwanted things do not occur. In this research activity, the researcher used a quantitative research method with a questionnaire survey method. With stages such as, the preparation stage, the implementation stage, the evaluation stage, and finally the validity test.